IETF and Internet standards. - Ohta, M.
The IETF (Internet Engineering Task Force) is a standardization body focused on the development of protocols used on IP-based networks. The IETF consists of many working groups and is managed by the Internet Engineering Steering Group (IESG), Internet Architecture Board (IAB), and Internet Society (ISOC). The IETF is different from most standardization bodies in that it is a totally open community with no formal membership, and its process is based on ?rough consensus running code?
Keywords: IAB; IESG; IETF; IP-based networks; ISOC; Internet Architecture Board; Internet Engineering Steering Group; Internet Engineering Task Force; Internet Society; Internet standards; Protocols; Rough consensus running code; Standardization body; Working groups